Limitações e contribuições do PLANFOR como política pública de qualificação profissional: o caso de Maceió. - Moreira, Maria de Lourdes da Silva (2007)
The research s objective is identify and analyze into public politics of work and income, specifically the PLANFOR, being aimed at to understand its contribution for the Social Development of Maceió. The analysis of this problematic one, on the basis of estimated and its objective delineated. This agreement passes for the critical analysis of the Pedagogical project, identifying to which implicit the educational paradigm in the PLANFOR, and continues in the empirical marks interviewing egresses of the courses of professional qualification, given for the Serviço Nacional de Aprendizagem Industrial (SENAI) of Maceió, and finishes with the comparative study of the results of the Bulhões (2001) research in Rio Grande do Sul state. From the accomplishment of the research it was observed that the PLANFOR was one innovative qualification politics, however had resulted shy in insert and replace worker in the market work, having little efficacious in this social development aspect.